Comparative evaluation of net setting time and radiopacity in Fuji II (GC-Japan) restorative glass ionomer and Iranian glass ionomer - Maryam Ghashami; Fahimeh Nouri; Soolmaz Heidari; Mahdis Mohammadpour; Monirsadat Mirzadeh; Nayereh Asgari (Wolters Kluwer Medknow Publications, 2022)
Background: Comparing the net setting time and radiopacity of an Iranian glass ionomer cement (GIC) and Fuji II (GC, Japan) according to ISO 9917-1:2007 standard. Materials and Methods: In this experimental/in vitro study, for both tests, we prepared 20 samples of Fuji II glass ionomer (self-cure restorative glass ionomer, batch number: 1608031, GC Corporation, Tokyo, Japan) and Iranian glass ionomer (Ava Tajhiz Dandan-Iran) at P/L of 2/7:1. Then, to determine the net setting time, we prepared a metal mold with dimensions of 10 mm in length, 8 mm in width, and 5 mm in height. Ninety seconds after mixing, the surface of the sample was subjected to the indenter, and the net setting time was recorded as the time elapsed between the end of the mixing and the time needle stopped making a complete circular indentation. To determine radiopacity, the specimens were poured into a mold with a diameter of 15 mm and thickness of 1 mm. Samples and a step wedge were irradiated with X-rays. Particle size analysis and Energy-dispersive X-ray spectroscopy (EDS) analysis were also done for both cements. Test results were investigated with SPSS and through independent t-test (P < 0.05). Results: The mean value of net setting time for Fuji II was 4.83 min and for the Iranian Glass ionomer was 3.83 min (P < 0.05). The mean value of radiopacity for Fuji II was 2.3 mmAL and for Iranian Glass ionomer was 1.9 mmAl (P < 0.05). Conclusion: Net setting time and radiopacity of the glass ionomers were within the range of ISO 9917-1:2007. If all properties of the Iranian cement are set appropriately in future investigations, we propose to use it instead of Fuji II GIC. This has the additional benefit of being cost-efficient as Iranian cement costs less than Fuji II cement.